THE FUCIK SPECTRUM FOR A COUPLED SYSTEM WITH NO CHANGING SIGN SOLUTIONS - Rojas Romero, Santiago César (2012)
In this work we study the Fucik spectrum for the following system of secondorder ordinary differential equationswhere Bu = 0 represents the Dirichlet or Newmann type boundary conditions. We study the case in which the nontrivial solutions (u,v) of the problem, keep their sign in the whole interval (0,1) and we prove: the Fucik spectrum for the Dirichlet problem is the union of a plane with an hyperbolic cylinder, while for the Newmann problem, the Fucik spectrum is formed by the Cartesian planes.